EVALUASI PELAKSANAAN PEMUNGUTAN RETRIBUSI KEBERSIHAN DI WILAYAH KECAMATAN LIMA PULUH KOTA PEKANBARU - Afriyani. M; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the Subdistrict of Pekanbaru that has not yet reached the target of retribution of cleanliness is a subdistrict of Fifty. With respect to the development of the population that are correlated with the production of the waste produced by each household, stores, offices, supplemented by informal economy activities in district of Fifty, then the problem becomes a problem of its own hygiene by the subdistrict of Pekanbaru Fifty .As for the purpose of this research is to find out and analyze to know and evaluate the implementation of hygiene in levy voting districts Fifty Pekanbaru and to know the factors restricting implementation evaluation of hygiene in levy voting districts Fifty Pekanbaru.This research was conducted at the Office of the head of Fifty Pekanbaru. The population in the penelitiaan this is the whole of the clerk in the Office of the head of Limappuluh Town of Pekanbaru that directly relate to implementation of a levy collection object hygiene, RT/RW that existed in the Passover Service Janitorial And Landscaping Pekanbaru and society. For informants in this study is the Head, the Secretary of the district, Kasi Trantib who receive retribution of cleanliness of their surroundings, the village head, RT and RW, Community Service and the cleanliness and Landscaping as a supervisory Institution. In accordance with the research objectives that have been mentioned above, then the required data, among other data of primary and secondary data. Data collection techniques to do with interview techniques, observation and the study of librarianship. A data analysis method used in this research is descriptive qualitative analysis method of.The results showed that the evaluation of cleanliness levy on ballot in district Fifty Pekanbaru then the average of the results of research conducted, the situation is already pretty well underway, voting in district hygiene retribution Fifty Pekanbaru seen from the aspect of effectiveness, sufficiency, equity, responsifitas and accuracy. As for the factors that affect voting in district hygiene retribution Fifty Pekanbaru, among others: the lack of ability and profesonalisme of HUMAN RESOURCE management in running the cleanliness and garbage collection levies, lack of facilities and infrastructure that support the implementation of the management of hygiene in the subdistrict of Pekanbaru Fifty Lack created communication between employees, the lack of interaction, coordination, and communication apparatus in the conduct and management of the levy of the poll of cleanliness and lack of coaching and supervision of Government retribution against officers of the Sub collector of hygiene.Keywords: Evaluation, Collection of A Levy On Hygiene